THE REPRESENTATION OF THE SON IN THE POETRY OF BLANCA VARELA: THE PLAYFUL, THE POWER AND THE GRIEF - Alvarado Taboada, Walter André (2019)
In this article we will analyze the poems "Fútbol", "Toy", "Casa de cuervos", "Dolor de corazón" and "Si me escucharas", from diferent collections of poems by the poet Blanca Varela, with the objective of investigating around the representation of the child, a fundamental aspect of the subject of motherhood. It is argued that this image articulates other significant elements in the work of the poet, such as play, power and grief, with what is constituted as a key element in the demystification of the story of happy motherhood.